1994
DOI: 10.1007/bf00175038
|View full text |Cite
|
Sign up to set email alerts
|

Influence of calcium on the effects of okadaic acid and its interaction with caffeine and theophylline in rat myometrium

Abstract: The effects of okadaic acid (OA), a monocarboxylic acid produced by marine dinoflagellates belonging to the genera Dinophysis and Prorocentrum, and their interactions with theophylline and caffeine were studied on the rat-isolated uterus in a calcium-containing medium and a calcium-free medium in the presence of 10(-3) M EGTA. Okadaic acid (5 x 10(-6) to 5 x 10(-5) M) induced a concentration-dependent contraction of the rat-isolated uterus corresponding, with 5 x 10(-5) M, to 142.3 +/- 6.1% (n = 7) of the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Candenas and coworkers [20] first reported that OA could inhibit and stimulate uterine contractions at low (100 nM) and high (5 M) concentrations, respectively. Okadaic acid-stimulated uterine contractions are partially inhibited when transmembrane Ca 2ϩ movement was inhibited with Ca 2ϩ -free media plus EDTA [21,22]. Administration of a cocktail of antagonists that block muscarinic, adrenergic, histaminergic, serotonergic, and opioid receptors were not found to alter significantly the stimulatory influence of 5-20 M OA [22].…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Candenas and coworkers [20] first reported that OA could inhibit and stimulate uterine contractions at low (100 nM) and high (5 M) concentrations, respectively. Okadaic acid-stimulated uterine contractions are partially inhibited when transmembrane Ca 2ϩ movement was inhibited with Ca 2ϩ -free media plus EDTA [21,22]. Administration of a cocktail of antagonists that block muscarinic, adrenergic, histaminergic, serotonergic, and opioid receptors were not found to alter significantly the stimulatory influence of 5-20 M OA [22].…”
Section: Discussionmentioning
confidence: 85%
“…Optical magnification: A1, B1, C1 ϭ ϫ100; A2, A3 ϭ ϫ400; B2, B3, C2, C3 ϭ ϫ1000. nM) inhibit contractions and higher concentrations cause a biphasic, contractile/relaxation response [21]. Effects of OA on myometrial strips would indicate that PP1 and/or PP2A are involved; however, no reports exist characterizing the PP in the myometrium.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Hence, PP2A inhibitors are expected to cause smooth muscle contraction. Paradoxically, inhibitor-based studies have shown that Յ1-3 M OA caused relaxation in rat, guinea pig, dog, pig, and bovine vasculature, rat myometrium, and bovine trachea smooth muscles (1,10,11,18,28,29,102,109,211,235). In myometrium, only Ͼ10 M OA produced contraction or temporary contraction and then relaxation, and these contractions were attributed to PP1 inhibition (10,28,29).…”
Section: Role Of Pp2a In Smooth Muscle Contractilitymentioning
confidence: 93%